-.3p-2.1=-3.6

Simple and best practice solution for -.3p-2.1=-3.6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -.3p-2.1=-3.6 equation:


Simplifying
-0.3p + -2.1 = -3.6

Reorder the terms:
-2.1 + -0.3p = -3.6

Solving
-2.1 + -0.3p = -3.6

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '2.1' to each side of the equation.
-2.1 + 2.1 + -0.3p = -3.6 + 2.1

Combine like terms: -2.1 + 2.1 = 0.0
0.0 + -0.3p = -3.6 + 2.1
-0.3p = -3.6 + 2.1

Combine like terms: -3.6 + 2.1 = -1.5
-0.3p = -1.5

Divide each side by '-0.3'.
p = 5

Simplifying
p = 5

See similar equations:

| 3x(x)+14x-5=0 | | (4200*2/3)6 | | -2x+7(0)=11 | | 2x+4=2x+3(-1x+2) | | 25x=5x-20 | | 2(n-2)=4n+6 | | 2x+3-20=500 | | 1.5x(6-4)= | | 3a=7c | | 2x+4=2x+3(-x+2) | | 500=100+3n | | 24n+72=288 | | log[2](3x+2)=log[3](12x+3) | | x(x)+7x-5=0 | | f(x)=2x^2+7x-1 | | s^2-13st-30t^2=0 | | 1.5x(6-4)=3 | | -7c-8(9-6c)= | | x(x)+16x+39=0 | | 5+2y=7 | | 6y-13=55 | | 8(y+9)=7y-3 | | solven+(n+1)+(n+2)=54 | | 25-n/2=10 | | 3(-1)-2(1/2) | | .2(-10x+25)=3x(-3-4) | | x^3+17x^2+41x+3=0 | | 25x-28=3x-10 | | x(x)+17x+60=0 | | x+4+8=4 | | 2sinx=3cosx+2 | | 5y-6/2=y-2-y/3 |

Equations solver categories